Rescue Therapy with a Proton Pump Inhibitor Plus Amoxicillin and Rifabutin for Helicobacter pylori Infection: A Systematic Review and Meta-Analysis. (25th May 2015) - Liu, Xiaoqun; Wang, Hui; Lv, Zhifa; Wang, Youhua; Wang, Ben; Xie, Yong; Zhou, Xiaojiang; Lv, Nonghua
Abstract : Background . To conduct a systematic review and meta-analysis of clinical trials for eradication of Helicobacter pylori ( H. pylori ) that included a treatment arm with a proton pump inhibitor, rifabutin, and amoxicillin. Materials and Methods . We selected clinical trials that examined the efficacy of H. pylori eradication therapies and included a study arm using the test regimen from major medical literature databases and abstracts from major gastroenterology meetings. We also did subgroup and sensitivity analyses. Results . Twenty-one studies were included in systematic review. The total eradication rates of the test regimen were 70.4% by intent-to-treat (ITT) and 72.0% by per-protocol (PP) analyses. The pooled odds ratio (OR) was 0.55 using fixed effects model (P = 0 . 283 ) for the test regimen versus other triple regimens. The total eradication rates were 68.4% for the test regimen and 81.9% in the control group by ITT, while the OR was 1.08 using random effects model (P = 0 . 019 ). The pooled eradication rate was 66.4% for the test regimen and 67.4% for the control group by ITT. The total adverse effects incidence were 25.1% for the test regimen. Conclusions . The test regimen for H. pylori rescue therapy may be not superior to control regimens in efficacy.